Scaling up rooftop solar power in India: The potential of municipal solar bonds - Saurabh Trivedi; Indro Ray; Gregor Vulturius; Amrita Goldar; Labanya Prakash J.; Sandeep Paul; Aarsi Sagar (Indian Council for Research on International Economic Relations (ICRIER), 2018)
India has made great progress in reaching its ambitious goal to scale up renewable energy capacity to 175 GW in 2022. Solar power plays a central part in achieving this goal and installations of utility scale power have seen a dramatic increase in the last few years. Rooftop solar, however, is lagging and more needs to be done to achieve its 40 GW capacity target by 2022. To meet the remaining rooftop target, this study estimates that the total capital requirement could be as high as USD 31.8 billion in addition to current subsidies and USD 39 billion excluding subsidies. The study suggests that municipalities can play a larger role in the acceleration of rooftop solar in India and proposes the use of municipal bonds to support the scale up of rooftop solar in India and details how such bonds could be designed and implemented. The study also applies proposed bond model to two Indian cities- Surat and New Delhi (NDMC) and illustrates how municipal bonds can significantly reduce the costs for rooftop solar and make it competitive and benefit different type of consumers in these cities.
Keywords: Q42; Q48; R51; 330; Municipal Finance; Municipal Bond; Rooftop Solar; Climate investment; energy finance; energy infrastructure; renewable energy